Wort Laut. - Daniels, Dieter; Holzer, Jenny; Mahlow, Dietrich; Schüppenhauer, Christel; Weiss, Christina (Köln : Galerie Schüppenhauer, 1989)
Barron, Stephan ; Berman, Mieczyslaw ; Beuys, Joseph ; Blobel, Wolfgang ; Brandmeier, Monika ; Brecht, George ; Brossa, Joan ; Burda, Vladimir ; Cage, John ; Carrega, Ugo ; Chopin, Henri ; Claus, Carlfriedrich ; Demnig, Gunter ; Dencker, Klaus Peter ; Duchamp, Marcel ; Dupuy, Jean ; Elfen, Fria ; Flynt, Henry ; Ganahl, Rainer ; Gappmayr, Heinz ; Grobman, Michail ; Hainke, Wolfgang ; Hansen, Al ; Hausmann, Raoul ; Ter Hell ; Henning, Reinhard ; Higgins, Dick ; Höch, Hannah ; Hoffmeister, Adolf ; Holzer, Jenny ; Houédard, Dom Sylvester ; Isgrò, Emilio ; Jandl, Ernst ; Janz, Angelika ; Jappe, Georg ; Johnson, Ray ; Katase, Kazuo ; Kiessling, Dieter ; Klophaus, Annalies ; Knowles, Alison ; Kolar, Jiri ; Kriwet, Ferdinand ; Kröger, Klaus ; Lacaz, Guto ; Löhr, Helmut ; Mau, Jürgen ; Miccini, Eugenio ; Mon, Franz ; Moorman, Charlotte ; Novak, Ladislav ; Olbrich, Jürgen O. ; Ox, Jack ; Paik, Nam June ; Patterson, Ben ; Prokot, Inge ; Rühm, Gerhard ; Sacharow-Ross, Igor ; Schäuffelen, Konrad Balder ; Schmidt, S.J. ; Schoening, Fanny ; Schwitters, Kurt ; Shimotani, Chihiro ; Spagnoli, Renato ; Takahashi, Shohachiro ; Thomkins, André ; Topolski, Andrew ; Tot, Endre ; Trinkewitz, Karl ; Ulrichs, Timm ; Ben ; Villeglé, Jacques ; Wada, Yoshima ; Weiss, Clemens ; Williams, Emmet ; Young, La Monte
biog. p. 133-135
Duits & Engels
Wort Laut, Galerie Schüppenhauer, Köln, 07.04 - 27.05.1989
boek